Revision of the genus Stichelia Zikán (Riodinidae: Riodininae: Symmachiini), with the description of a new species from southern Brazil - Silva Dias, Fernando Maia; Dolibaina, Diego Rodrigo; Mielke, Olaf Hermann Hendrik; Casagrande, Mirna Martins (Zootaxa, 2013)
A new species from southern Brazil, Stichelia catarinensis sp. nov., is described and lectotypes for Charis dukinfieldia Schaus, 1902 and Phaenochitonia bocchoris suavis Stichel, 1911 are designated. Phaenochitonia bocchoris suavis Stichel, 1911 syn. nov. is considered synonymous with Amarynthis bocchoris Hewitson, 1876. Two species groups are recognized: "cuneifascia" species group, including S. cuneifascia and S. catarinensis sp. nov., and "bocchoris" species group, including S. bocchoris, S. dukinfieldia and S. pelotensis. Additionally, a taxonomic dichotomous key and morphologic illustration for the species of the genus are provided.